Neutrophil-to-lymphocyte, platelet-to-lymphocyte ratios and systemic immune-inflammation index in patients with post-traumatic stress disorder - Gözde Yontar; Elif Aktan Mutlu (BMC Psychiatry)
Abstract Background Low-grade systemic inflammation has been reported in many psychiatric diseases and is described as a non-severe state of the inflammatory response. Post-traumatic stress disorder (PTSD) is a chronic psychiatric disorder characterized by symptoms of avoidance, re-experiencing and hyperarousal that develop secondary to a serious traumatic event. The trauma itself creates psychological and biological changes in the individual, apart from PTSD. This complex situation has still not been clarified and researchers have tended to research on inflammatory processes. Systemic immune inflammation index (SII), as a new index related to inflammation, is a comprehensive value based on peripheral lymphocyte, neutrophil and platelet counts. SII has been used as a marker of subclinical inflammation and prognosis in various studies. Although the presence of inflammation in PTSD was tried to be demonstrated through cytokines, inflammatory variables such as neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and SII, which are low-cost and easily shown in routine examinations, have not been studied before. Method We compared PTSD patients with healthy controls. 160 subjects (80 PTSD and 80 controls) were enrolled for study. All patients were evaluated with Structured clinical study form for DSM-V Axis 1 disorders. Exclusion criteria were as follows: presence of PTSD symptoms shorter than one month, presence of psychiatric comorbidity, being diagnosed with psychotic disorder, bipolar disorder, autism spectrum disorder, presence of mental retardation, being under psychotropic drug treatment, presence of a neurological disease that may cause serious disability (epilepsy, cerebrovascular disease), migraine, presence of organic brain damage, smoking, alcohol and substance use disorder, presence of a chronic disease such as diabetes mellitus, hypertension, hyperlipidemia, chronic lung diseases, being in pregnancy and breastfeeding, presence of heart disease were determined as exclusion criteria. Additionally, patients with diseases that could affect the leukocyte count (hematopoietic disease, malignancy, acute infection, acute or chronic renal failure, liver failure) and medication use (chemotherapy, history of glucocorticoid use in the last three months) were not included in the study. Patients who smoked more than fifteen cigarettes per day and had a body mass index > 30 were also excluded. SII is calculated as follows; SII = platelet count x neutrophil count / lymphocyte count. Results Sociodemographic data were comparable among groups. Neutrophil and platelet levels of PTSD patients were significantly higher than controls although both groups’ values were in normal range. Moreover, NLR, PLR and SII were significantly higher in PTSD group. Conclusion We found that NLR, PLR and SII values, which are easily calculable and cost-effective markers of systemic inflammation, were significantly higher in PTSD patients than in the control group. These values may be considered to identify patients who may benefit from adjuvant anti-inflammatory pharmacological treatment on top of psychotherapeutic treatment.